The influence of Gymnema sylvestre on the elevation of blood levels of lipids after administration of animal fat in male wistar rats - DOI: 10.4025/actascibiolsci.v26i3.1602 - Silva, Elizete Rosa dos Santos (2008)
The aim of the present experiment was to investigate the influence of Gymnema sylvestre (Gs) on the elevation of blood levels of lipids after administration of animal fat in male Wistar rats (230–250g). The animals, which were fasted for 22h, were separated in five groups that received (8:00 a.m) intragastric administration of: 1) 2ml of pork fat Batavo® /kg of body weight (PFB); 2) PFB+500mg/kg of Gs body weight (Gs 500mg); 3) PFB + 1g/kg of Gs body weight (Gs 1 g); 4) Gs 500mg; 5) Gs 1g. The animals were sacrificed 30min after the administration of these substances. No significant differences were verified in the serum concentration of total lipids, triglycerides and cholesterol in the animals, which received PBF in the presence or absence of Gs 500mg or Gs 1g. Therefore, the results showed that Gs could not affect the intestinal absorption of lipids